Transcriptome Profiling Combined With Activities of Antioxidant and Soil Enzymes Reveals an Ability of Pseudomonas sp. CFA to Mitigate p-Hydroxybenzoic and Ferulic Acid Stresses in Cucumber - Zhang, Yue; Chen, Chang-Xia; Feng, Hui-Ping; Wang, Xiu-Juan; Roessner, Ute; Walker, Robert; Cheng, Zeng-Yan; An, Yan-Qiu; Du, Binghai; Bai, Ji-Gang (Frontiers in Microbiology, 2020)
Continuous-cropping leads to obstacles in crop productivity by the accumulation of p-hydroxybenzoic acid (PHBA) and ferulic acid (FA). In this study, a strain CFA of Psuedomonas was shown to have a higher PHBA- and FA-degrading ability in media and soil and the mechanisms underlying this were explored. Optimal conditions for PHBA and FA degradation by CFA were 0.2 g/l of PHBA and FA, 37°C, and pH 6.56. Using transcriptome analysis, complete pathways that converted PHBA and FA to acetyl coenzyme A were proposed in CFA. When CFA was provided with PHBA and FA, we observed upregulation of genes in the pathways and detected intermediate metabolites including vanillin, vanillic acid, and protocatechuic acid. Moreover, 4-hydroxybenzoate 3-monooxygenase and vanillate O-demethylase were rate-limiting enzymes by gene overexpression. Knockouts of small non-coding RNA (sRNA) genes, including sRNA 11, sRNA 14, sRNA 20, and sRNA 60, improved the degradation of PHBA and FA. When applied to cucumber-planted soil supplemented with PHBA and FA, CFA decreased PHBA and FA in soil. Furthermore, a reduction of superoxide radical, hydrogen peroxide, and malondialdehyde in cucumber was observed by activating superoxide dismutase, catalase, glutathione peroxidase, ascorbate peroxidase, glutathione reductase, dehydroascorbate reductase, and monodehydroascorbate reductase in seedlings, increasing the reduced glutathione and ascorbate in leaves, and inducing catalase, urease, and phosphatase in the rhizosphere. CFA has potential to mitigate PHBA and FA stresses in cucumber and alleviate continuous-cropping obstacles.